2017
DOI: 10.1039/c7sc02395b
|View full text |Cite
|
Sign up to set email alerts
|

Selective arc-discharge synthesis of Dy2S-clusterfullerenes and their isomer-dependent single molecule magnetism

Abstract: A method for the selective synthesis of sulfide clusterfullerenes Dy2S@C2n is developed. Addition of methane to the reactive atmosphere reduces the formation of empty fullerenes in the arc-discharge synthesis, whereas the use of Dy2S3 as a source of metal and sulfur affords sulfide clusterfullerenes as the main fullerene products along with smaller amounts of carbide clusterfullerenes. Two isomers of Dy2S@C82 with Cs(6) and C3v(8) cage symmetry, Dy2S@C72-Cs(10528), and a carbide clusterfullerene Dy2C2@C82-Cs(6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
68
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 93 publications
3
68
1
1
Order By: Relevance
“…[91] EMFs based single molecule magnets have been a rapid developing research area in the recent years. [46,47,92] In 2012, Greber and Dunsch [91] found that DySc 2 N @C 80 exhibited a hysteresis of magnetization with zero-field quantum tunneling of magnetization, which was the first reported EMF based single molecule magnet. Later, they found that the ferromagnetic coupling of individual dysprosium moments in Dy 2 ScN@C 80 is even higher than that in DySc 2 N @C 80 .…”
Section: Magnetic Fullerenesmentioning
confidence: 99%
See 2 more Smart Citations
“…[91] EMFs based single molecule magnets have been a rapid developing research area in the recent years. [46,47,92] In 2012, Greber and Dunsch [91] found that DySc 2 N @C 80 exhibited a hysteresis of magnetization with zero-field quantum tunneling of magnetization, which was the first reported EMF based single molecule magnet. Later, they found that the ferromagnetic coupling of individual dysprosium moments in Dy 2 ScN@C 80 is even higher than that in DySc 2 N @C 80 .…”
Section: Magnetic Fullerenesmentioning
confidence: 99%
“…However, no SMM property was found for Dy 3 N@C 80 due to the fully frustrated ferromagnetic coupling in it. [93] Popov and Yang studied the SMM properties of a series of EMFs including Dy 2 TiC 2 @C 80 , [94] Dy 2 TiC@C 80 , [94] TbNC@C 76 , [92] TbNC@C 82 , [95] Dy 2 S@C 82 [47] and Dy 2 ScN@C 80 . [93,96] They found that Dy 2 ScN @C 80 is the best single-molecule magnet among all the above-mentioned EMFs.…”
Section: Magnetic Fullerenesmentioning
confidence: 99%
See 1 more Smart Citation
“…Single‐molecule magnetism is a phenomenon involving the slow relaxation of magnetization in molecules with a bistable magnetic ground state and has been a hot topic in the field of molecular magnetism during the last decades . Indeed, some lanthanide‐clusterfullerenes exhibit single‐molecule magnetism, which is most robust in dysprosium‐clusterfullerenes …”
Section: Introductionmentioning
confidence: 99%
“…1) which is a S-ligated single-ion magnet with hysteresis loops open up to 7 K and a magnetisation reversal barrier of U eff = 638 K, which is unprecedented in the very small family of S-ligated Dy(III) singleion magnets (see Table 1). [14][15][16][17][18][19][20] Compound 1 was isolated by using the cage-like ligand N-(3,5-di-tert-butyl-2-hydroxybenzyl)-N,N-bis(2-pyridylmethyl)amine (HL ON3 ) (see ESI †). 21 Our synthetic strategy generates one short Dy-O bond, to direct the magnetic anisotropy, 22 and three longer Dy-N bonds.…”
mentioning
confidence: 99%